2005
DOI: 10.1158/0008-5472.can-04-4662
|View full text |Cite
|
Sign up to set email alerts
|

Milk Thistle and Prostate Cancer: Differential Effects of Pure Flavonolignans from Silybum marianum on Antiproliferative End Points in Human Prostate Carcinoma Cells

Abstract: Extracts from the seeds of milk thistle, Silybum marianum, are known commonly as silibinin and silymarin and possess anticancer actions on human prostate carcinoma in vitro and in vivo. Seven distinct flavonolignan compounds and a flavonoid have been isolated from commercial silymarin extracts. Most notably, two pairs of diastereomers, silybin A and silybin B and isosilybin A and isosilybin B, are among these compounds. In contrast, silibinin is composed only of a 1:1 mixture of silybin A and silybin B. With t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
208
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 209 publications
(219 citation statements)
references
References 35 publications
7
208
0
4
Order By: Relevance
“…Recently we showed the effect of isosilybin B and its other isomers namely silybin A, silybin B and isosilybin A (Figure 1a) on secreted PSA levels in LNCaP cells after 72 h treatment (Davis-Searles et al, 2005). Here, first we examined a comparative effect of these diastereoisomers, following 24 h of their treatment, on both secreted and intracellular PSA levels in PCA LNCaP, 22Rv1 and LAPC4 cells.…”
Section: Effect Of Isosilybin B and Its Other Isomers On Psa And Ar Lmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently we showed the effect of isosilybin B and its other isomers namely silybin A, silybin B and isosilybin A (Figure 1a) on secreted PSA levels in LNCaP cells after 72 h treatment (Davis-Searles et al, 2005). Here, first we examined a comparative effect of these diastereoisomers, following 24 h of their treatment, on both secreted and intracellular PSA levels in PCA LNCaP, 22Rv1 and LAPC4 cells.…”
Section: Effect Of Isosilybin B and Its Other Isomers On Psa And Ar Lmentioning
confidence: 92%
“…seeds, and is widely known for its hepatoprotective and cancer chemopreventive action (Wellington and Jarvis, 2001;Agarwal, 2002, 2006;Deep et al, 2006). Recently, we have isolated and purified from silymarin seven distinct flavonolignans namely silybin A, silybin B, isosilybin A, isosilybin B, silydianin, silychristin, isosilychristin and one flavonoid taxifolin ; and assessed their biological effects on many antiproliferative end points in human PCA cell lines (Davis-Searles et al, 2005). Isosilybin B ranked the most potent flavonolignan for nearly all end points including inhibition of prostate-specific antigen (PSA) secretion (Davis-Searles et al, 2005), which is used as a clinical tool in screening, diagnosis and treatment decisions for human PCA (Nelson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such naturally occurring agent is silibinin (Fig. 1B), a major flavonolignan component in silymarin, which is a mixture of flavonoids present in milk thistle; the chemical structures of these isomers were recently reported by us (8). Several studies by us and others have shown the cancer-preventive and therapeutic efficacy of silymarin and silibinin in different animal tumor models and cancer cells in culture (9).…”
Section: Introductionmentioning
confidence: 91%
“…Several studies on sily-marin declared its valuable effects in treatment of type II diabetic patients which was attributed to its antioxidant effect [5]. Moreover, inhibition of cancer cell growth in human prostate, skin, breast, and cervical cells was reported [6]. A number of methods utilizing HPLC and capillary electrophoresis were used for partial separation of the six components of silymarin [7,8], but the majority of these methods suffered from incomplete separation of silychristin, silydianin, and the two diastereoisomers of silybin and isosilybin.…”
Section: Introductionmentioning
confidence: 99%